MO247: Exogen ATP has a Suppressive Effect on CD4+-T-Cells In Aav-Patients And Healthy Controls. (3rd May 2022) - Haase, Alexandra; Yang, Dai; Dolff, Sebastian; Witzke, Oliver; Kribben, Andreas; Wilde, Benjamin
Abstract: BACKGROUND AND AIMS: Anti-neutrophil-cytoplasmatic-antibody-associated vasculitis (AAV) is a life-threatening autoimmune disease. It is a necrotizing vasculitis of small- and medium-sized vessels. T-cells play a pivotal role in pathogenesis and mediating damage in the vessels. Exogen ATP (adenosine triphosphate) is normally in a low nanomolar range. Under inflammatory conditions, various cells can release ATP to the extracellular department. In this case, ATP is a DAMP (damage-associated molecular pattern), but its effect on disease mechanisms in AAV is not well understood. It is the aim of the study to determine the effect of exogenous ATP on T-cells in healthy controls and AAV-patients. METHOD: A total of 22 AAV-patients in remission and 13 healthy controls were recruited. Peripheral blood mononuclear cells (PBMC) were isolated and then labeled with a tracking dye. The PBMC were cultured for 3 days with different concentrations of ATP in presence or absence of anti-CD3/CD28 stimulation. After 3 days, the cells were restimulated with PMA/Ionomycin and Brefeldin A for 4 hours. Cytokine production and cell proliferation were assessed by flow cytometry. Baseline was defined as T-cell proliferation in absence of exogenous ATP. The fold change was calculated by: T - cell proliferation with ATPT - cell proliferation without ATP . The P-value for paired values was calculated by the Wilcoxon matched-pairs signed rank test. The P-value for unpaired groups was calculated by the Mann Whitney U -test. RESULTS: The mean T-cell proliferation of CD4 + -T-cells for healthy controls was significantly different comparing 0 µM ATP and 500 µM ATP (mean proliferated fraction, 0 µM ATP versus 500 µM ATP: 40.48% versu 22.58%, P = .0002). In presence of ATP, a suppression of T-cell proliferation was found in patients and healthy controls (patients versus healthy controls, fold change T-cell proliferation from baseline with 50 µM ATP: 0.81 ± 0.03 versus 0.79 ± 0.03, P = .60; 125 µM ATP: 0.75 ± 0.03 versus 0.70 ± 0.04, P = .38; 250 µM ATP: 0.68 ± 0.03 versus 0.59 ± 0.05, P = .17; 500 µM ATP: 0.53 ± 0.03 versus 0.54 ± 0.05, P = .77); the higher the concentration of ATP, the stronger the suppression of proliferation. IFNγ + -CD4 + -T-cells of healthy controls were also suppressed by exogenous ATP (0 µM ATP versus 500 µM ATP, CD4 + T-cells: %IFNγ + : 19.94% versus 10.59%, P = .0002). INFγ production by CD4 + -T-cells was reduced after addition of ATP in both patients and healthy controls (patients versus healthy controls, fold change CD4 + -IFNγ + -T-cells from baseline with 50 µM ATP: 0.69 ± 0.04 versus 0.64 ± 0.04, P = 0.45; 125 µM ATP: 0.62 ± 0.04 versus 0.58 ± 0.04, P = .63; 250 µM ATP: 0.62 ± 0.04 versus 0.49 ± 0.04, P = .11; 500 µM ATP: 0.59 ± 0.05 versus 0.51 ± 0.05, P = .56). CONCLUSION: Exogenous ATP induced suppression of T-cells in healthy controls and might be important for the maintenance of immunotolerance. DAMP-mediated inhibitory mechanisms were functional in AAV-patients in remission.